Effect of Maca root (Lepidium meyenii) on some biochemical and antioxidant parameters in rats with experimental polycystic ovary syndrome - Celikdemir, Nisanur; Mamur, Maide Nur; Ceribasi, Ali Osman; Ustun, Irem; Yilmaz, Seval; Kaya, Emre (Univ Zulia, Facultad Ciencias Veterinarias, 2025)
In this study, the potential therapeutic effect of Maca root (Lepidium Meyenii) on oxidative damage and histopathological changes in ovaries induced by experimental polycystic ovary syndrome (PCOS) in rats was evaluated. The study involved thirty-five female Sprague Dawley rats, each aged 2.5 months. These rats were allocated into five distinct groups. The first group did not receive any treatment or intervention. Carboxymethyl cellulose (CMC) (1%) was applied to 2nd group. Maca root was applied to the 3rd group at a dose of 2 gkg-1d-1 body weight by gavage for 7 days (d). 1 mgkg-1d-1 letrozole (PCOS agent) dissolved in 1% CMC was applied to the 4th group by gavage for 21 d. Letrozole and maca root were applied together to the 5th group. Maca root application was started on the 15th d of letrozole application and was applied for 7 d, while letrozole was applied for 21 d starting 14 d before maca root application and both applications were terminated on the 22nd d. In the PCOS group, malondialdehyde (MDA) levels were observed to be elevated compared to the control group, whereas reduced glutathione (GSH) levels, along with the activities of catalase (CAT), glutathione peroxidase (GSH-Px), glutathione-S-transferase (GST), and superoxide dismutase (SOD), were found to be reduced. In the PCOS+maca root group, differences were determined compared to the PCOS applied group, and the all parameter values were found to be close to the control group values (except GSH-Px and Follicle-Stimulating Hormone (FSH)). The number of atretic follicles were significantly decreased in the PCOS group and PCOS+maca group compared to the control group (P <= 0.01). It was noted that the number of cystic follicles increased statistically significantly in the PCOS groups compared to the other groups (P <= 0.001). In the development of PCOS-related ovarian toxicity and oxidative stress, PCOS may contribute to a discrepancy between oxidants and antioxidants, while Maca root may help alleviate the severe side effects caused by PCOS.
Efecto de la raíz de maca (Lepidium meyenii) sobre algunos parámetros bioquímicos y antioxidantes en ratas con síndrome de ovario poliquístico experimental
Keywords: PCOS; Lepidium Meyenii; malondialdehyde; testosterone; follicle